Karakteristik Perkembangan Peserta Didik Anak Sekolah Dasar Usia 12 Tahun (Studi Kasus: Fanny Azizah): INDONESIA - rahma rahma; Khatulistiwa; Rahmah; Salsa Fadilla (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to describe the developmental characteristics of 12-year-old students through a case study of a student named Fanny Azizah. The study used a qualitative approach with a case study method, with data collection techniques in the form of interviews and documentation. Data analysis was carried out through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Fanny's physical development is in the good category, characterized by strong physical stamina, stable motor coordination, and fine motor skills that support learning activities. In the cognitive aspect, Fanny entered the early formal operational stage according to Piaget's theory, characterized by the ability to understand cause-effect relationships, draw simple conclusions, and learn effectively using visual media. Psychomotor development also developed optimally, seen from her agility of movement, neat writing skills, and accuracy in school assignments. From a social perspective, Fanny demonstrated the ability to adapt, cooperate, build positive relationships, and have high empathy towards peers. Emotional development is in the fairly stable category, Fanny is able to express and manage emotions, although still sensitive to criticism and requires support from parents and teachers. Overall, the study concluded that Fanny's development in all aspects is at an optimal stage and requires ongoing support from both the family and school environment to support her readiness for early adolescence.